Design, Optimization, Manufacture and Characterization of Milbemycin Oxime Nanoemulsions - Ze-En Li; Yang-Guang Jin; Shao-Zu Hu; Yue Liu; Ming-Hui Duan; Shi-Hao Li; Long-Ji Sun; Fan Yang; Fang Yang (Pharmaceutics)
Background: Despite the rapid development of nanoemulsions in recent years, no method has been established for the preparation of milbemycin oxime nanoemulsions. Milbemycin oxime is a widely used macrolide antibiotic in veterinary medicine, particularly for treating parasitic infections in animals such as dogs. However, its poor solubility in water limits its bioavailability and therapeutic efficacy. Developing a nanoemulsion formulation can enhance its solubility, stability, and bioavailability, offering a more effective treatment option. Methods: In this experiment, oil-in-water (O/W) milbemycin oxime nanoemulsions were successfully prepared by the phase inversion composition (PIC) method using ethyl butyrate as the oil phase, Tween-80 as the surfactant, and anhydrous ethanol as the co-surfactant. The region of O/W nanoemulsions was identified by constructing a pseudo-ternary phase diagram and, based on this, was screened by determining the droplet size, polydispersity coefficient, and zeta potential of each preparation. Results and Conclusions: The finalized formulation had a 2:1 ratio of surfactant to co-surfactant and a 7:3 ratio of mixed surfactant to oil, and its droplet size, polydispersity index (PDI), and zeta potential were 12.140 ± 0.128 nm, 0.155 ± 0.015, and −4.947 ± 0.768 mV, respectively. Transmission electron microscopy confirmed the spherical uniform distribution of droplets, and the nanoemulsions passed thermodynamic stability tests. The in vitro release of milbemycin oxime nanoemulsions followed first-order kinetic equations. In conclusion, nanoemulsions are an interesting option for the delivery of poorly water-soluble molecules such as milbemycin oxime.